Limonin induces apoptosis of HL‐60 cells by inhibiting NQO1 activity. Issue 4 (2nd March 2021) - Chen, Yunyi; Liang, Jiaojiao; Liang, Xiao; Chen, Jiebiao; Wang, Yue; Cao, Jinping; Sun, Chongde; Ye, Jiaming; Chen, Qingjun
Abstract: Limonin is an important bioactive substance in citrus fruits, especially in seeds, which has great potential in cancer prevention and treatment. In order to explore the anticancer activity based on interaction between limonin and NQO1, Human promyelocytic leukemia cells (HL‐60) were studied in vitro. We found that limonin could inhibit proliferation and promote apoptosis of HL‐60 cells, and the effect was positively correlated with its dosage. Western blot results showed that limonin could activate the endogenous apoptosis pathway mediated by mitochondria via up‐regulating pro‐apoptotic proteins (Bax, cytochrome c, Caspase3, and Caspase9) and down‐regulating anti‐apoptotic proteins (Bcl‐2), thus inhibiting the proliferation of HL‐60 cells and promoting apoptosis, which further proved the anticancer activity of limonin from the molecular mechanism. At the same time, limonin down‐regulated the expression of NQO1, indicating that limonin may indirectly act on the apoptosis pathway by regulating the expression activity of antioxidant enzymes in vivo, thus exerting its inhibitory effect on tumor cells, which provides an idea for the molecular mechanism that natural products can indirectly exert their anticancer effect by regulating the activity of antioxidant enzymes. Abstract : Limonin, a citrus nutrient factor, was used as the subject material, which showed a proliferation inhibitory effect on HL‐60 cells. Mechanism exploration found that this effect was caused by activating the apoptosis pathway through inhibiting NQO1 expression.